Infantile undifferentiated sarcomas: a diagnostic and therapeutic challenge – two case reports and literature review - Aleksandra Stanio; Jakub Czarny; Sandra Rutkowska; Katarzyna Adamczewska-Wawrzynowicz; Łukasz Młynarczyk; Agnieszka Stróżyk; Katarzyna Jończyk-Potoczna; Alicja Bartkowska-Śniatkowska; Jacek Wachowiak; Katarzyna Derwich; Olga Zając-Spychała (Acta Oncologica)
Background: Soft tissue undifferentiated sarcomas (STUS) are an ultra-rare and heterogenous group of mesenchymal neoplasms often lacking known genetic abnormalities with a marked vulnerability towards intensive therapy such as invasive surgery and high dose chemotherapy. Despite aggressive treatment, they are usually associated with dismal outcomes.